The Clinical Information System That Effects The Patients' Satisfaction Of The Healthcare Services - Sri Hartono; Yanto Ramli; Rina Astini; C. Catur Widayati; Anees Janee Ali (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2024)
This research intends to understand and investigate how to increase patients' satisfaction by implementing the clinical information system and by looking at the service quality, green environment, and patients' perceptions to provide better patient satisfaction concerning healthcare services. The data collection is done through the distribution of questionnaires in Jakarta, Indonesia. This research is based on descriptive and verification methods; the sample is determined through Purposive Sampling, and the method analysis technique is Partial Least Square (PLS). The research results show that patients' perception significantly influences clinical system information compared to quality services and a green environment to achieve patient satisfaction. Healthcare clinics need to implement the clinical system information to assist the healthcare workers in providing quality patient services.